Baroreflex dysfunction induced by microgravity: potential relevance to postflight orthostatic intolerance - Ertl, A. C.; Diedrich, A.; Biaggioni, I.; Robertson, D. (Clinical autonomic research, 2000)
Microgravity imposes adaptive changes in the human body. This review focuses on the changes in baroreflex function produced by actual spaceflight, or by experimental models that simulate microgravity, e.g., bed rest. We will analyze separately studies involving baroreflexes arising from carotid sinus and aortic arch afferents ("high-pressure baroreceptors"), and cardiopulmonary afferents ("low-pressure receptors"). Studies from unrelated laboratories using different techniques have concluded that actual or simulated exposure to microgravity reduces baroreflex function arising from carotid sinus afferents ("carotic-cardiac baroreflex"). The techniques used to study the carotid-cardiac baroreflex, using neck suction and compression to simulate changes in blood pressure, have been extensively validated. In contrast, it is more difficult to selectively study aortic arch or cardiopulmonary baroreceptors. Nonetheless, studies that have examined these baroreceptors suggest that microgravity produces the opposite effect, ie, an increase in the gain of aortic arch and cardiopulmonary baroreflexes. Furthermore, most studies have focus on instantaneous changes in heart rate, which almost exclusively examines the vagal limb of the baroreflex. In comparison, there is limited information about the effect of microgravity on sympathetic function. A substantial proportion of subjects exposed to microgravity develop transient orthostatic intolerance. It has been proposed that alterations in baroreflex function play a role in the orthostatic intolerance induced by microgravity. The evidence in favor and against this hypothesis is reviewed.